Implementasi Manajemen Bimbingan dan Konseling di MTs NU TBS Kudus - Bayan, Muhammad Aqib Khusnul (Konseling Edukasi : Journal of Guidance and Counseling, 2021)
Implementation of Guidance and Counseling Management at MTs NU TBS Kudus. This study aims to determine the implementation of guidance and counseling management at MTs TBS Kudus. The method in this study uses a qualitative descriptive method with a case study approach at MTs TBS Kudus. The collected data was then analyzed by the data analysis technique used in this study is a descriptive analysis in the field of the Miles and Huberman model. The results showed that the implementation of the management of counseling guidance at MTs TBS Kudus has been going well. The program planning stage is by analyzing student needs and problems, analyzing school conditions, determining goals, understanding and determining materials, determining time and place, determining facilities and planning budgets. The organizing stage is carried out by selecting a competent counselor. The stage of implementing guidance and counseling at MTs TBS Kudus by carrying out counseling services in accordance with SOP equipped with supporting activities. The evaluation stage of the BK program is by evaluating programs and then improving them again.Keywords: Implementation, Counseling Guidance Management, MTs TBS Kudus